Linking entrepreneurial orientation to firm performance of small and medium-sized manufacturing firms in Sabah: moderating effect of the government’s role / Melvin Mojikon - Mojikon, Melvin (Institute of Graduate Studies, UiTM, 2016)
Entrepreneurial Orientation (EO) has been defined as the strategic orientation employed by firms that deal with identifying ways and creating a specific set of methods with the help of various styles of making decision, where numerous ways and practices of entrepreneurial aspects can be eventually realized. Hence, this study was conducted based on the phenomenon experienced by a number of manufacturing firms in the State of Sabah, Malaysia within the context of Small and Medium-Sized Enterprises (SMEs). The EO, moreover, was deemed as a multidimensional construct encompassing five dimensions (i.e. autonomy, competitive aggressiveness, innovativeness, proactiveness, and risk taking). The manufacturing sector in Sabah vitally contributes to the growth of the economy in Sabah, but the sales growth performance was found to be inconsistent based on the eleventh position in the ranking, especially among SMEs involved in the manufacturing sector in Sabah compared to those from the other states in Malaysia; albeit there was more help from the government side, challenges were still faced in improving their sales growth performance. With that, the objectives of this study were to determine the relationship between EO and firm performance (i.e. sales growth), as well as to determine the moderating influence factor of the government’s role in the relationship between EO and firm performance. The method applied in this study had been the quantitative method. In this study, proportionate stratified random sampling, as well as the drop-off and collecting technique was applied. The location of this study involved five divisions (i.e. Kudat Division, West Coast Division, Interior Division, Sandakan Division, and Tawau Division) in the State of Sabah…